Strategi Pemerintahan Daerah Kota Padang Panjang dalam Menjaga Keberlanjutan Lahan dan Pangan - Putra Tri Rezeki, Angga; Frinaldi, Aldri (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
This study analyzes the strategies that have been implemented by the Local Government of Padang Panjang City to maintain land sustainability and food security amid the challenges of converting agricultural land to non-agricultural uses. The reduction in agricultural land area in Padang Panjang City from 805 hectares in 2018 to 654 hectares in 2023 has resulted in a decline in local food production, making the city increasingly dependent on food supplies from other regions. This research employs a descriptive qualitative approach, where data is collected through in-depth interviews and documentary studies. The results indicate that the Padang Panjang City Government has implemented various strategies, including the strategy of establishing sustainable agricultural land, increasing food production, educating on the use of technology in agriculture, and promoting agricultural land as a tourist village. However, several challenges remain, such as the lack of community awareness regarding the importance of land sustainability, limited land that can be allocated for agriculture, and insufficient coordination in policy implementation. This study provides recommendations to enhance policy effectiveness and cooperation between the government and the community to maintain land sustainability and food security in Padang Panjang City.